Waseda Boys’ Phonological Interference of Indonesian Food Names In Nihongo Mantappu Vlogs - Saskiya, Rikma; Tresnasari, Ningrum (Universitas Diponegoro, 2022)
Interference is a mistake generally made by second language learners because they are influenced by their first language ability. Meanwhile, phonological interference is a mistake that occurs at the sound level due to changes in phonemes influenced by knowledge of the sound system in the first language. This paper discusses the errors of second language learners in understanding the sound changes that occur in the language they are learning. This study aims to describe the forms and factors that cause phonological interference committed by “Tes Wasedaboys Tulis Nama Makanan Indonesia! Ngakak Banget!”. The method used in the research is descriptive qualitative method with the theory referring to Weinrich's interference theory (1953). The data collection method used is the listening method with free listening technique. Based on the analysis that has been done, the form of phonological interference that occurs in the YouTube video on the Nihongo Mantappu channel entitled “Tes Wasedaboys Tulis Nama Makanan Indonesia! Ngakak Banget!” is divided into 2 classifications, namely 9 data of vowel phoneme interference and 8 data of consonant phoneme interference. Each interference is divided based on the addition of phonemes as much as 3 data, based on phoneme changes as much as 7 data, and based on phoneme reduction as much as 7 data. The factors that cause phonological interference are (1) bilingualism of speech participants which amounted to 3 data, (2) differences in vowel sounds and writing methods which amounted to 11 data, (3) carrying the mother tongue which amounted to 3 data. <a href=